Β-Galactosidase instructed supramolecular hydrogelation for selective identification and removal of senescent cells. Issue 50 (4th June 2019) - Xu, Tengyan; Cai, Yanbin; Zhong, Xinglong; Zhang, Le; Zheng, Debing; Gao, Zhengfeng; Pan, Xianmei; Wang, Fuqiang; Chen, Minsheng; Yang, Zhimou
Abstract : We introduced a novel strategy of β-galactosidase instructed supramolecular hydrogelation for selective identification and removal of senescent cells. Abstract : The identification and removal of senescent cells is very important to improve human health and prolong life. In this study, we introduced a novel strategy of β-galactosidase (β-Gal) instructed peptide self-assembly to selectively form nanofibers and hydrogels in senescent cells. We demonstrated that the in situ formed nanofibers could alleviate endothelial cell senescence by reducing p53, p21, and p16 INK4a expression levels. We also demonstrated that our strategy could selectively remove senescent endothelial cells by inducing cell apoptosis, with an increase in the BAX/BCL-2 ratio and caspase-3 expression. Our study reports the first example of enzyme-instructed self-assembly (EISA) by a sugar hydrolase, which may lead to the development of supramolecular nanomaterials for the diagnosis and treatment of many diseases, such as cancer, and for other applications, such as wound healing and senescence.